MK‐1 Apatite: A New Potential Reference Material for (U‐Th)/He Dating. Issue 2 (6th March 2019) - Wu, Lin; Shi, Guanghai; Danišík, Martin; Zhang, Zhiyong; Wang, Yinzhi; Wang, Fei
Abstract : The (U‐Th)/He dating technique has been widely used for several decades to constrain the timing of low temperature geological processes. Recent research has shown that the commonly used reference material (the Durango apatite) often yields dispersed fragment dates that are beyond analytical uncertainties. Here, we report a new apatite (U‐Th)/He dating reference material, MK‐1, which was collected from the Mogok metamorphic belt in Burma. Electron probe microanalysis and backscattered electron images of two randomly selected fragments indicate that this apatite is chemically and structurally homogeneous. We performed single‐grain (U‐Th)/He dating on thirty randomly selected fragments of this material. (U‐Th)/He dating results from multiple laboratories show that fragments of the MK‐1 apatite megacryst yielded reproducible results, with a mean date of 18.0 ± 0.2 Ma. The Th/U ratio of this apatite is homogeneous. Nine randomly selected fragments registered a narrow range of effective uranium (eU) mass fractions (326–354 μg g −1 ), with a mean value of 336.6 ± 10.3 μg g −1 . Twenty‐four in situ (U‐Th)/He dates yielded a mean value of 18.0 ± 0.2 Ma (MSWD = 0.41), indistinguishable from the results obtained by the conventional method. All the results suggest that this apatite has the potential to become a new reference material for (U‐Th)/He geochronology. Key Points: Conventional and in situ (U‐Th)/He dating methods were conducted on apatite megacrysts MK‐1 from Myanmar. Apatite MK‐1 yielded a reproducible (U‐Th)/He date of 18.0 ± 0.2 Ma with an homogeneous Th/U ratio of 0.7. MK‐1 has the potential to become a new reference material for both conventional and in situ (U‐Th)/He geochronology.